Phytosome: A Revolution in Herbal Drug Delivery System - Singh, Arpita; Pratap Singh, Anil; Verma, Neeraj (Asian Journal of Chemistry, 2011)
The efficiency of any herbal medication is dependent on delivery of effective level of the therapeutically active compound. But severe limitations exist in their bioavailability when administered orally or by topical application. The bioavailability can be improved by the use of delivery systems, enhancing the rate and the extent of drug solubilizing into aqueous intestinal fluids and the capacity to cross the lipid rich biomembranes. Phytosomes are newly introduced herbal formulations developed to incorporate standardized plant extracts or water soluble phytoconstituents into phospholipids to produce lipid compatible molecular complexes and so vastly improve their absorption and bioavailability. Phytosomes exhibit better pharmacokinetic and pharmacodynamic profile than conventional herbal extracts. It is also often known as herbosomes. This article apart from providing information regarding the advantages and physiochemical properties of phytosomes gives various simple research techniques in the preparation and its optimization.